Leptin-inhibited neurons in the lateral parabrachial nucleus do not alter food intake or glucose balance - Seahyung Park; Kevin W. Williams; Jong-Woo Sohn (Animal Cells and Systems, 2022)
The lateral parabrachial nucleus (LPBN) has been shown to be involved in the suppression of appetite at the pharmacological, optogenetic and chemogenetic levels. However, the signalling that mediates activation of these neurons in physiological conditions has been hindered by difficulties in segregating different cell populations in this region. Using reporter mice, we identify at the electrophysiological level the effects of an anorexic hormone, leptin, on leptin receptor (ObR)-expressing neurons in the LPBN (LPBNObR neurons). Application of leptin caused inhibition in a subpopulation of LPBNObR neurons. This effect was mediated by an increased potassium conductance and was also accompanied by a decrease in excitatory synaptic input onto these neurons. However, mimicking the inhibitory effects of leptin on LPBNObR neurons through chemogenetics led to no changes in feeding or glucose levels, which suggests that leptin action on LPBNObR neurons may not be sufficient to regulate these metabolic aspects.